Finding Least Cost Hyperpaths in Multimodal Transit Networks: Methodology, Algorithm, and Large-Scale Application - Verbas, İ. Ömer; Mahmassani, Hani S. (Transportation research record, 2015)
This paper presents a least cost hyperpath algorithm that captures the complexities that arise in a transit network because of the number of transfers, the standing and overcrowding penalties, the availability of walking and biking in addition to the transit modes, and the mode-specific limitations such as availability of bike parking. The problem was formulated as a mathematical program, and then a hybrid label setting–correcting algorithm was proposed as a solution. The multi-modal time- and approach-dependent algorithm does not require spatial or temporal expansion of the network; this feature results in good computational performance for large-scale applications. Scenario runs performed on the large-scale Chicago Transit Authority network, in Illinois, validate the accuracy and performance of the algorithm.